\({x - 1 \over 3}\)-\({2x - 5 \over 4}\)=\({5 \over 12}\) + \({x \over 6}\)

I'm extremely lost... I'm not really sure how to do this.

I know that the LCD: (3)(4)(6)... right?

Am I just basically multiplying the LCD with each fraction?

The text got this: \({4(x - 1) - 3(2x - 5) = 5 + 2x}\)

How do I get this answer?

Guest Apr 3, 2018

#1**+2 **

The LCD is actually just 3*4. This is because 12/6 = 2. When you multiply this to each fraction, you get the answer that the text gave.

Mathhemathh
Apr 3, 2018

#2**+2 **

\(\frac{x-1}{3}-\frac{2x-5}{4}=\frac{5}{12}+\frac{x}{6}\\ \text{Multiply BOTH sides by the lowest common denominator which is 12}\\ 12\left[\frac{x-1}{3}-\frac{2x-5}{4}\right]=12\left[\frac{5}{12}+\frac{x}{6}\right]\\ \frac{12(x-1)}{3}-\frac{12(2x-5)}{4}=\frac{12*5}{12}+\frac{12x}{6}\\ 4(x-1)-3(2x-5)=5+2x\\ 4x-4-6x+15=5+2x\\ etc\)

Melody
Apr 3, 2018